Embedded programming and real-time signal processing of swimming strokes - Le Sage, T.; Bindel, A.; Conway, P. P.; Justham, L. M.; Slawson, S. E.; West, A. A. (Sports Engineering, 2011)
The research outlined in this paper was conducted to allow real-time processing, transmission and presentation of data to swimming coaches and subsequently their swimmers in a training environment, focused on providing information relevant to strokes in free swimming. This was achieved using a wearable wireless sensor and embedded programming techniques, using accelerations involved in the swimming stroke to provide relevant features for coaches. Current methods used do not offer real-time response to coaches, which results in the lack of real-time feedback and significantly increased post-session analysis time. Filtering and signal processing algorithms are described here, which allow real-time data analysis to be embedded within a wireless sensor node. The system significantly reduces the time for processing acquired data and has delivered a novel monitoring device suitable for operation within the harsh environment of the pool.